Duduk & Tonton 2: Online Screening and Discussion with the Filmmakers - Chong Lee, Yow; Hong Ling, Tan (Mini Film Festival, 2021)
Programmed by Yow Chong Lee, the festival programmer for 17th Mini Film Festival, this screening featured 6 short films made by Malaysian filmmakers, namely: